The silence of the drowned and the journalistic ethos - Echenique Dominguez, Carlos André (2017)
This paper focuses the silencing of voices in news production in Posadas, Argentina (Primera Edición and Territorio Digital) and Porto Alegre, Brazil, (Zero Hora and Correio do Povo), and investigates the media coverage of 2003 until 2014, in relation to the construction of two hydroelectric plants on the border between both countries, Brazil and Argentina, on the Uruguay river. The analysis indicates the absence of the riverside dwellers’ voices, who are affected by the project. Finally, the article stand up for the idea journalism makes a great contribution to the discussion of environmental complexity.